Characteristics of nest sites of skuas and kelp gull in the Antarctic Peninsula - Quintana, Ruben Dario; Travaini, Alejandro (Journal of Field Ornithology)
We investigated nest-site selection of sympatrically breeding skuas (Catharacta spp.) and Kelp Gulls (Larus dominicanus) in the Antarctic Peninsula. We evaluated habitat preferences of nesting skuas and gulls in a patchy landscape by counting the numbers of nests in each of ten habitat types. Additionally, we evaluated the importance of 11 habitat variables (known to be influential to the reproductive success of marine birds) on nest-site selection by skuas and gulls. Both skuas and Kelp Gulls did not used habitat types in proportion to their availability. Skuas tended to nest in highlands with a north-northwest aspect, and in depressed areas with stable substrata. Kelp Gulls nested exclusively on coastal cliffs and pebble beaches, with no difference in tendency to use either habitat. Skua and gull nest sites were differentiated by elevation, percent of vegetation cover, slope, and microtopography. Grasses (for Kelp Gull), mosses (for skuas), and rockiness were the main variables predicting differential use of the available environment. Factors such as type of nest materials, proximity to foraging areas, social interactions, and presence of other species, among others, probably also affect nest-site selection for both skuas and gulls at Cierva Point, Antarctic Peninsula. Fil: Quintana, Ruben Dario. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Caldas. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Biologicas; Colombia Fil: Travaini, Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Caldas. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Biologicas; Colombia